Use of concrete block waste as aggregate in structural concrete block - Bussolaro, Ana Paula Favretto; Gabriel, Elaise; Meller, Gabriela; Rigon, Ursula Maira Maciel; Leão, Marlon (Revista Eletrônica em Gestão, Educação e Tecnologia Ambiental, 2022)
Civil construction generates a large amount of waste and consequently faces problems in the final destination of these materials. Among the most common materials, we can highlight concrete as the second largest waste generator, therefore being a problem for society. In this context, this research analyzed the use of residues of concrete blocks as aggregate in the structural block of the building. For this, structural concrete blocks with different recycled waste contents were molded and later submitted to tests of resistance to compression, water absorption and dimensional analysis. The results showed that the addition of recycled residues caused an increase in water absorption and a reduction in compressive strength as the conventional aggregate was replaced by the recycled aggregate. It was concluded that concrete residues can be applied as an aggregate of structural concrete block provided that it respects certain limits of residue content. The application of the technique can consume the entire residue coming from the manufacture of structural concrete blocks.